Different immune response of dendritic cells of newborns of allergic and healthy mothers to bacterial stimuli - Hrdý, Jiří; Novotná, Olga; Petrásková, Petra; Boráková, Kristýna; Prokešová, Ludmila (Folia microbiologica, 2019)
Continuous increasing incidence of allergic diseases is calling for identifying early prognostic markers pointing to increased risk of allergy development and establishing protocols for preventive strategies limiting allergy development in predisposed individuals. It is important to better understand the critical events occurring in early postnatal life, especially the interaction of a newborn with microbial compounds important for the maturation of the neonatal immune system and setting immunoregulatory responses as well. Dendritic cells (DC) together with the cytokine microenvironment play an important role in priming of immune responses. The capacity of monocyte-derived DC (moDC) from cord blood of children of healthy and allergic mothers to respond to microbial antigens (Escherichia coli O86 (EcO86) and delipidated Bacillus firmus (DBF)) was tested by flow cytometry and quantitative real-time PCR. Both EcO86 and DBF were able to promote maturation of moDC, but moDC of children of allergic mothers expressed higher levels of activation markers CD80 and CD83. Increased gene expression of IL-6 and lower expression of indol-amine 2,3 dioxygenase were observed in moDC of neonates of allergic mothers, in comparison to healthy ones. A higher gene expression and an increased presence of activation markers on moDC of newborns of allergic mothers indicate a generally higher reactivity of these cells, possibly enabling easier development of inappropriate immune response after an allergen encounter.
Keywords: Male; Biomarkers; Mothers; monocyty; Antigens, Bacterial; kultivované buňky; Dendritic Cells; Humans; Antigens, Surface; biologické markery; Fetal Blood; novorozenec; mužské pohlaví; Female; Cytokines; Monocytes; antigeny bakteriální; Cells, Cultured; ženské pohlaví; Hypersensitivity; dendritické buňky; alergie; fetální krev; cytokiny; lidé; antigeny povrchové; matky; Infant, Newborn